Mutual fund flows and seasonalities in stock returns - Wagner, Moritz; Lee, John Byong-Tek; Margaritis, Dimitris (Journal of Banking & Finance, 2022)
We propose a flow-based explanation for two long-standing anomalies in empirical finance – Sell in May and the January effect. We find that mutual fund flows exhibit similar seasonal patterns as stock returns. After controlling for fund flows both calendar effects become insignificant. We provide new evidence on what drives this correlation. We show that return seasonality is due to unanticipated fund flow driven by uninformed (flow-motivated) retail investor trading. Active funds indicate flow-induced price pressure with a corresponding reversal of the effect, while passive funds suggest feedback trading instead. These seasonalities are remarkably pervasive, exhibiting little variation across different types of stocks, and are equally strong in periods of either high or low sentiment.